ANALISIS USAHA-USAHA PEMASARAN DALAM MENGHADAPI PERSAINGAN BISNIS USAHA KECIL MENENGAH (Kasus Bisnis Rendang Telur di Kotamadya Payakumbuh) - Nenti Oucis Sara; Kasmiruddin, " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is done on the business in town payakumbuh rendang egg. as for the formulation of the problem, namely how the right marketing efforts in order to face competition in the present.This research uses descriptive qualitative analysis method using the theory put forward by some experts on marketing efforts. in this study using the indicator of product packaging, pricing, promotion and distribution of product implementation rendang egg. techniques of data collection and survey interviews. census sampling techniques.Sources of data obtained by questionnaires and interviews with informants. And the results obtained can be seen that the marketing efforts rendang egg in Payakumbuh categorized Not Good.Keywords : Lending Policies, PT. Permodalan Siak